(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Now day’s perpetual pavement design becomes the alternative for design of long life pavement. There are many constraints of pavement design in order to perform the long life pavement. Due to the ability of long life pavement designs, since from last 15 years there are many research investigation carried out over perpetual asphalt pavement designs all over the world. Long life pavement success is aim of perpetual pavement design all over the world in any country. While designing the perpetual pavement design with goal of long life success, there are some additional factors like climate imposes the extra challenge. Hence designing perpetual pavement is main research problem of this research work. The scope of this research project involves the evaluation of the perpetual pavement design in the real time road networks and highways and its comparison with conventional pavement design. The research is based on a case study, which enables consideration of the severe impact of the year-round environmental conditions that affect pavements in different countries. For this research work, as we are not actually involving practical analysis part, we are referring the recent research projects in which organizations such as the MTO (Ministry of Transportation of Ontario), OHMPA (Ontario Hot Mix Producers Association), NSERC (Natural Science and Engineering Research Council of Canada), Stantec Lt., McAsphalt Industries Ltd., Capital Paving, and Aecon collaborated with the University of Waterloo Centre of Pavement and Transportation Technology (CPATT). The assessment methodology consisting of economic and structural assessment protocol development for both classical existing asphalt pavement design as well as perpetual pavement designs.